Remote Sensing- Based Assessment of Climatic Decades in Baghdad City Using Statistical Trend Analysis and Variance Testing (ANOVA) - Ali K. Resen (Iraqi Journal of Physics)
This study analyzes long-term trends in temporal data from 1980 to 2020, encompassing four decades to assess the impacts of climate change on the environment and ecosystems. The NASA power data access viewer provided data, including wind, temperature, solar radiation, atmospheric pressure, precipitation, and humidity. Statistical analysis methods, including trend analysis and ANOVA, were utilized to evaluate the disparities among time courses. Linear regression models were employed to conduct trend analysis for each decade, assessing changes in climate parameters. An analysis of variance (ANOVA) was performed over four decades. The findings demonstrate that no statistically significant differences exist in the examined climate parameters over the decades. However, trend analysis of average monthly data over four decades indicates that local climates have undergone changes in recent years. The monthly analysis of six parameters revealed an increase in wind speed of 1% during the second decade, 8% during the third decade, and 4% during the fourth decade. The temperature increased at monthly rates, especially during the study period, with a significant rise of 1.7% from 2010 to 2020. In the last decade, solar radiation decreased by 0.0003%, likely due to pollution, given Baghdad's status as an urban area with considerable industrial activity and high population density. The pressure escalated over a span of four decades, peaking between 2010 and 2020, which corresponds to a change rate of 5.3%. The study period observed a decrease in humidity, with change ratios of 2.6% in the first decade and 0.5% in the fourth decade.